Pengaruh Komitmen, Religiusitas dan Keterlibatan Guru Terhadap Kesejahteraan Subyektif Guru Madrasah Ibtidaiyah, Juwana, Pati, Jawa Tengah - Sri Lestari; Mohammad Fauzan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of the study is to analyze and explain the influence of (1) teachers' commitment to teachers' subjective wellbeing ; (2) religiosity to the teachers' subjective wellbeing; (3) teacher engagement to teachers' the subjective wellbeing. This type of research is explanatory. The sample was 101 teachers of Madrasah Ibtidaiyah in Juwana, Pati, Central Java. Data collection uses a questionnaire using a google form, which is then sent to each respondent. Data analysis uses multiple linear regression. For the purpose of analysis, instrument tests are carried out; model test and hypothesis test with the help of SPSS software. The findings of this study are (1) The teacher commitment has a positive effect on the teacher subjective wellbeing (2) Religiosity has a positive effect on the subjective wellbeing, (3) Teacher Engagement has a positive effect on the subjective subjective wellbeing of Madrasah Ibtidaiyah teachers in Juwana, Pati, Central Java. Based on the findings of the research, the school principal in an effort to improve the subjective wellbeing. of teachers, needs to create a conducive work environment so that space is created for teachers to increase commitment, religiosity and teacher involvement